Study of femtosecond laser post-processing regimes for dispersion tailoring of fiber Bragg gratings - Imogore, Timothy O.; Kraemer, Ria G.; Goebel, Thorsten A.; Matzdorf, Christian; Richter, Daniel; Nolte, Stefan (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Nonlinearly chirped fiber Bragg gratings (FBGs) are essential components for ultrafast fiber lasers, acting as tailored higher order dispersive elements. They can be realized using femtosecond IR lasers, which offers independency from fiber core photosensitivity. The nonlinear spatial variation of the grating period along the grating length might be generated either by using a nonlinearly chirped phase mask or direct inscription techniques [1]. However, these techniques have some drawbacks with respect to production possibilities, stability, reproducibility, flexibility, or a combination of these. As an alternative approach, the dispersion characteristics of a chirped FBG inscribed by femtosecond laser pulses using a simple chirped phase mask can be fine-tuned by femtosecond laser post-processing of selected grating regions [2]. It thus combines the advantages of stability and reproducibility with flexibility. For this, no further modifications of the inscription setup or complex phase mask designs are required. The dispersion of the already inscribed chirped FBG is tuned by modifying the DC average refractive index ( Δn dc ). However, the applicability of the aforementioned technique needs to be further explored by a detailed understanding of the evolution of the Δn dc with respect to the femtosecond laser post processing parameters. In this paper, we present for the first time an investigation on the relationship between femtosecond laser post-processing parameters (such as the pulse energy, scanning speed, repetition rate and the grating strength) and the resulting refractive index change. The inscription and post-processing was realized using a Ti:sapphire ultrafast laser (λ = 800 nm, Spectra Physics) providing a pulse duration of 100 fs.
CRIS-Team Scopus Importer:2023-04-20